Design and Construction Study of a Shell and Tube Heat Exchanger Prototype as an Ethanol Purification Distillation Unit: Studi Rancang Bangun Prototipe Alat Penukar Kalor Type Shell and Tube Sebagai Unit Distilasi Pemurnian Etanol - Asnawi; Rahman, Abdul; Islami, Nurul; Junianti, Dwi (E-Journal Universitas Malikussaleh, 2025)
Bioethanol is a renewable energy that has the potential to replace fuel oil with a high octane value. A common problem experienced in the process of making bioethanol is the difficulty of obtaining pure ethanol levels. So the purification process is an important factor in producing bioethanol which can function as fuel. The distillation process aims to separate ethanol from the ethanol-water mixture. The boiling point of ethanol is 78ºC and the boiling point of water is 100ºC so that by heating to a temperature of 78ºC using the distillation method, ethanol can be separated from the ethanol-water mixture. In this research, a distillation device has been successfully designed which consists of a heater, boiler and heat exchanger. The shell and tube type heat exchanger is designed with a capacity of 2 liters. The tube side uses 20 copper pipes with a diameter of 1/4 in, a thickness of 0.5 mm, a length of 400 mm, and a pitch distance of 13 mm. On the shell side, a 3 in diameter PVC pipe with a length of 500 mm is used. Capable of transferring heat with effectiveness reaching 89% with ethanol content of 92%.